213k views
4 votes
Describe and solve the error 3x - 5 + 2x² + 9x = 3x + 2x² + 9x - 5​

User Suguna
by
5.3k points

1 Answer

5 votes

Answer:

3x - 5 + 2x² + 9x = 3x + 2x² + 9x - 5​ = TRUE = 2 x^2 + 12 x - 5

Explanation:

left: Simplify the following:

2 x^2 + 9 x + 3 x - 5

Grouping like terms, 2 x^2 + 9 x + 3 x - 5 = 2 x^2 + (3 x + 9 x) - 5:

2 x^2 + (3 x + 9 x) - 5

3 x + 9 x = 12 x:

Answer: 2 x^2 + 12 x - 5

_______________________

Simplify the following:

2 x^2 + 9 x + 3 x - 5

Grouping like terms, 2 x^2 + 9 x + 3 x - 5 = 2 x^2 + (3 x + 9 x) - 5:

2 x^2 + (3 x + 9 x) - 5

3 x + 9 x = 12 x:

Answer: 2 x^2 + 12 x - 5

User Dean Fenster
by
5.8k points